FREQUENCY OF OSTEOPOROSIS IN CHRONIC LIVER DISEASE PATIENTS - KOUR , K; KHAN , MI; SAJJAD , J; KHAN , MA; RIAZ, N; ANJUM, IH (Biological and Clinical Sciences Research Journal, 2024)
Chronic liver disease (CLD) is a significant health concern often associated with systemic complications, including osteoporosis. Early detection of osteoporosis in CLD patients is critical for preventing fractures and improving quality of life. Objective: To determine the frequency of osteoporosis in patients with chronic liver disease (CLD).Methods: This cross-sectional study was carried over six months, from May 2024 to November 2024, and included 80 patients with confirmed CLD. Participants aged 30 to 60 years were recruited from outpatient and inpatient settings. Dual-energy X-ray absorptiometry (DEXA) was used to measure bone mineral density (BMD), which was then classified into normal or osteoporosis categories based on T-scores. Demographic and clinical data were collected through structured evaluations. Results: Mean age was 46.15 ± 9.46 years. Among the cohort, 20 patients (25.0%) had osteoporosis. Osteoporosis was associated with increasing age (p = 0.001), female gender (p = 0.004), lower BMI (p = 0.0001) and Child-Pugh Class (p = 0.02).Conclusion: Osteoporosis is a prevalent complication in CLD, associated with older age, female gender, lower BMI, and advanced disease severity.